2023
DOI: 10.1111/cts.13580
|View full text |Cite
|
Sign up to set email alerts
|

A phase I randomized, double‐blinded, placebo‐controlled study assessing the safety and pharmacokinetics of RIPK1 inhibitor GFH312 in healthy subjects

Abstract: Receptor‐interacting protein kinase 1 (RIPK1) mediates necroptosis and inflammation in various pathophysiologies, emerging as a pharmacological target for neurodegenerative and inflammatory indications. This phase I, first‐in‐human, placebo‐controlled study evaluated the safety, pharmacokinetics (PKs), and pharmacodynamics (PDs) of GFH312, an RIPK1 inhibitor, in healthy adults. Subjects received GFH312 as a single ascending dose up to 500 mg (part I) or once‐daily repeated doses up to 200 mg for 14 days (part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Overall, SAR443820 was well‐tolerated in this study, without raising any safety concerns in the dose escalation and safety profile was consistent with that of other brain penetrant RIPK1 inhibitors. 9 , 26 Mild abnormalities in laboratory values were observed related to SAR443820, however, the safety data do not suggest a dose‐dependent trend. Two cases of asymptomatic ALT increase (≥2‐fold ULN but limited <3‐fold ULN) were reported in this study, but none were considered as clinically relevant.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Overall, SAR443820 was well‐tolerated in this study, without raising any safety concerns in the dose escalation and safety profile was consistent with that of other brain penetrant RIPK1 inhibitors. 9 , 26 Mild abnormalities in laboratory values were observed related to SAR443820, however, the safety data do not suggest a dose‐dependent trend. Two cases of asymptomatic ALT increase (≥2‐fold ULN but limited <3‐fold ULN) were reported in this study, but none were considered as clinically relevant.…”
Section: Discussionmentioning
confidence: 85%
“…Two cases of asymptomatic ALT increase (≥2‐fold ULN but limited <3‐fold ULN) were reported in this study, but none were considered as clinically relevant. Similar to SAR443820, other RIPK1 inhibitors, such as SAR443060, 9 GSK2982772, 20 and GFH312, 26 were found to be well‐tolerated with no reports of ALT abnormalities in healthy participants. Taken together, it may be assumed that the liver function abnormalities may not be a mechanism‐based consideration.…”
Section: Discussionmentioning
confidence: 93%
“…Recent preclinical and clinical studies have unquestionably recognized the roles of RIPK1 in neurogenerative disorders ( Li & Yuan, 2023 ; Scarpellini et al, 2023 ; Xu, Zhang & Zhuang, 2023 ). In a phase I clinical trial, a small molecule GFH312 showed significant RIPK1 inhibition with a tolerability profile comparable to that of the placebo ( Lickliter et al, 2023 ). Despite demonstrating promise in targeting RIPK1 for the treatment of Alzheimer’s disease, SAR443060, another orally bioavailable CNS penetrant investigational agent, was abandoned due to long-term toxicities ( Vissers et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%